Angiogenic Endothelial Cell Signaling in Cardiac Hypertrophy and Heart Failure - Gogiraju, Rajinikanth; Bochenek, Magdalena L.; Schäfer, Katrin (Frontiers in Cardiovascular Medicine, 2019)
Endothelial cells are, by number, the most frequent cell type in the heart and active players in cardiac physiology and pathology. Coronary angiogenesis plays a vital role in maintaining cardiac vascularization and perfusion during physiological and pathological hypertrophy. On the other hand, a reduction in cardiac capillary density with subsequent tissue hypoxia, cell death and interstitial fibrosis contributes to the development of contractile dysfunction and heart failure, as suggested by clinical as well as experimental evidence. Although the molecular causes underlying the inadequate (with respect to the increased oxygen and energy demands of the hypertrophied cardiomyocyte) cardiac vascularization developing during pathological hypertrophy are incompletely understood. Research efforts over the past years have discovered interesting mediators and potential candidates involved in this process. In this review article, we will focus on the vascular changes occurring during cardiac hypertrophy and the transition towards heart failure both in human disease and preclinical models. We will summarize recent findings in transgenic mice and experimental models of cardiac hypertrophy on factors expressed and released from cardiomyocytes, pericytes and inflammatory cells involved in the paracrine (dys)regulation of cardiac angiogenesis. Moreover, we will discuss major signaling events of critical angiogenic ligands in endothelial cells and their possible disturbance by hypoxia or oxidative stress. In this regard, we will particularly highlight findings on negative regulators of angiogenesis, including protein tyrosine phosphatase-1B and tumor suppressor p53, and how they link signaling involved in cell growth and metabolic control to cardiac angiogenesis. Besides endothelial cell death, phenotypic conversion and acquisition of myofibroblast-like characteristics may also contribute to the development of cardiac fibrosis, the structural correlate of cardiac dysfunction. Factors secreted by (dysfunctional) endothelial cells and their effects on cardiomyocytes including hypertrophy, contractility and fibrosis, close the vicious circle of reciprocal cell-cell interactions within the heart during pathological hypertrophy remodeling.